2017
DOI: 10.3389/fpsyg.2017.00927
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Outcome of the Psychotherapy Compared to Antidepressant Therapy in Anxiety and Depression Disorders: A Meta-Analysis

Abstract: The most prevalent mental disorders, anxiety and depression, are commonly associated with structural and functional changes in the fronto-limbic brain areas. The clinical trials investigating patients with affective disorders showed different outcome to different treatments such as psychotherapy or pharmacotherapy. It is, however, still unexplored how these interventions approach affect the functional brain. This meta-analysis aims to compare the effects of psychotherapy compared to antidepressant therapy on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 83 publications
0
23
0
Order By: Relevance
“…Neural mechanisms of treatment response to BA treatment.-Research into the neural patterns of treatment response in depression are consistent with the notion that depression is a disorder of corticolimbic networks. A recent meta-analysis of task-based and resting state fMRI studies suggests that both psychotherapy and medication result in posttreatment decreases in activation of the right inferior frontal gyrus, superior frontal gyrus, ACC, and right insula (Kalsi et al, 2017). However, unique correlates of treatment response were also identified.…”
Section: Neural Correlates Of Reward Processing In Depression and Anhmentioning
confidence: 99%
See 2 more Smart Citations
“…Neural mechanisms of treatment response to BA treatment.-Research into the neural patterns of treatment response in depression are consistent with the notion that depression is a disorder of corticolimbic networks. A recent meta-analysis of task-based and resting state fMRI studies suggests that both psychotherapy and medication result in posttreatment decreases in activation of the right inferior frontal gyrus, superior frontal gyrus, ACC, and right insula (Kalsi et al, 2017). However, unique correlates of treatment response were also identified.…”
Section: Neural Correlates Of Reward Processing In Depression and Anhmentioning
confidence: 99%
“…However, unique correlates of treatment response were also identified. Changes in activation in the right paracingulate gyrus differentiated between response to medication versus psychotherapy; decreased activation predicted improved response under medication, while increased activation predicted improved response during psychotherapy (Kalsi et al, 2017). However, studies in this meta-analysis only addressed the effects of interventions on broadly defined depression severity.…”
Section: Activation As the Mechanism Of Change In Bamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis on neuroimaging findings of neural change in brain networks associated to emotion regulation after psychotherapy of depression by Messina et al ( 2013 ) detected consistent changes in the DMPFC and in the posterior cingulated gyrus/precuneus, and in several areas in the temporal lobes in depression. A further meta-analysis by Kalsi et al ( 2017 ) compared the effects of psychotherapy compared to antidepressant therapy on brain activity in depression. They found that patients undergoing psychotherapy showed an increase in the right paracingulate activity while pharmacological treatment led to a decrease of activation of this area.…”
Section: Neuropsychodynamic Approach To Treatment Of Depressionmentioning
confidence: 99%
“…It is known that over the course of treatment, CBT leads to a shift in in emotional bias, which is indeed one of its key treatment goals. It was suggested that, in general terms, CBT works mainly by increasing top-down control in executive and dorsal attention networks, but also, although to a lesser extent, by reducing overreactivity of ventral cortico-limbic structures, the latter being main mode of action of pharmacological treatments (DeRubeis et al 2008, Kalsi et al 2017. Unfortunately studies investigating early shifts in emotional processing during CBT are scarce and were applied to panic disorder (Reinecke et al 2014), not depression.…”
Section: Can Cognitive Neuropsychological Model Be Applied To Non-phamentioning
confidence: 99%